PAI TEACHER CREATIVITY IN USING E-LEARNING LEARNING METHODS IN SMA - Mardianto Mardianto; Mohammad Al Farabi; Sri Wahyuni Nainggolan (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
This study aims to analyze the creativity of Islamic Religious Education teachers in using e-learning learning methods, PAI teacher strategies in using e-learning learning methods, supporting factors and inhibiting PAI teachers' creativity in using e-learning learning methods, and the achievement of student learning outcomes in SMA Negeri 1 Wampu, Langkat Regency. This research method is qualitative, namely the technique used to examine the condition of natural objects where the researcher is the key instrument. Data collection was carried out systematically through data collection techniques by observation, interviews, and documentation studies. In addition, this study also uses phenomenology. At SMA Negeri 1 Wampu, Langkat Regency, the teacher carries out the learning process by delivering uniformed learning materials with the help of learning media. Due to COVID-19, face-to-face learning has to be limited. The learning process is carried out using WhatsApp group media, line, and reports. The learning process is carried out using the Offline Method, which deals with students who do not have the facilities and infrastructure. PAI teacher creativity in motivating students to learn via e-learning at SMA Negeri 1 Wampu Langkat Regency by applying various learning methods, using interesting applications for students. For example, making attractive PowerPoint Presentation media, making games in the learning process, and giving prizes for students who focus on the learning process.Keywords: Creativity; E-Learning Method. AbstrakPenelitian ini bertujuan untuk menganalis kreativitas guru Pendidikan Agama Islam dalam menggunakan metode pembelajaran e-learning, strategi guru PAI dalam penggunaan metode pembelajaran e-learning, faktor pendukung dan penghambat kreativitas guru PAI dalam menggunakan metode pembelajaran e-learning, dan pencapaian hasil belajar siswa di SMA Negeri 1 Wampu Kabupaten Langkat. Metode penelitian ini adalah kualitatif, yaitu metode yang digunakan untuk meneliti pada kondisi objek yang alamiah dimana peneliti adalah sebagai instrumen kunci. Pengambilan data yang dilakukan secara sistematis melalui teknik pengumpulan data dengan observasi, wawancara dan studi dokumentasi. Selain itu penelitian ini juga menggunakan fenomenologi. Di SMA Negeri 1 Wampu Kabupaten Langkat guru melakukan proses pembelajaran dengan cara penyampaian materi pembelajaran yang diseragamkan dengan bantuan media pembelajaran. Adanya covid mengakibatkan pembelajaran tatap muka harus dibatasi. Proses pembelajaran dilakukan dengan media whatshaap grup, line dan melalui laporan. Proses pembelajaran dilakukan dengan metode Luring Method yaitu untuk menyiasati siswa yang tidak memiliki sarana dan prasarana. Kreativitas guru PAI dalam memotivasi siswa untuk belajar via e-learning di SMA Negeri 1 Wampu Kabupaten Langkat dengan menerapkan metode pembelajaran yang bervariasi, menggunakan aplikasi-aplikasi yang menarik bagi siswa. Sebagai contoh, membuat media Power Point Presentation yang menarik, membuat game dalam proses pembelajaran, dan memberikan hadiah bagi siswa yang fokus pada saat proses pembelajaran. Kata Kunci: Kreatifi; E-Learning.